Angiogenesis, multitarget kinase inhibitors and non-small cell lung cancer: a lesson from MONET1 trial - Mendivil, Alejandro Navarro; Rodriguez, Pablo Martinez; Felip, Enriqueta (Translational Lung Cancer Research; Vol 2, No 1 (February 14, 2013): Translational Lung Cancer Research, 2013)
Angiogenesis, the development and formation of new blood vessels, has been described as one of the hallmarks of cancer, playing an important role in tumor growth, invasion and metastasis (1-4). Several signaling pathways are implicated, such as the vascular endothelial growth factor (VEGF) pathway and platelet-derived growth factor (PDGF) pathway (5). Inhibiting tumor angiogenesis is a therapeutic strategy that has been tested in different solid tumors, including non-small cell lung cancer (NSCLC) (6-8).